2014
DOI: 10.1002/clc.22342
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Dronedarone in Patients Previously Treated With Other Antiarrhythmic Agents

Abstract: Background: Currently available antiarrhythmic drugs (AADs) for the prevention of atrial fibrillation (AF)/atrial flutter (AFL) suffer from incomplete efficacy and poor tolerability. In patients previously treated with a class Ic agent, dronedarone decreased the risk of recurrence by 31.4% (HR: 0.69; 95% CI: 0.53-0.89; P = 0.004), whereas in patients previously treated with sotalol, dronedarone showed a trend toward a decrease of risk of recurrence (HR: 0.86; 95% CI: 0.67-1.11; P = 0.244). Dronedarone was equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…There are major differences in patient characteristics between clinical trials [6,18,[29][30][31] and real-world analyses [19,32], as clinical trials are designed to evaluate the efficacy and safety of a drug under ideal conditions. For example, clinical trials have specific inclusion or exclusion criteria, and ensure that patients have continuous follow-up and good compliance.…”
Section: Discussionmentioning
confidence: 99%
“…There are major differences in patient characteristics between clinical trials [6,18,[29][30][31] and real-world analyses [19,32], as clinical trials are designed to evaluate the efficacy and safety of a drug under ideal conditions. For example, clinical trials have specific inclusion or exclusion criteria, and ensure that patients have continuous follow-up and good compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Dronedarone has a similar chemical structure to amiodarone and is thus referred to as a secondgeneration amiodarone. Further research conducted by Guerra et al, confirmed that dronedarone is the most effective AAD for treating AF and is even tolerated by patients who previously presented with an inability to tolerate other AADs [29]. According to Ezekowitz et al, dronedarone can prevent the occurrence of AF [30].However, there are studies that indicate that dronedarone treatment in patients with AF is less effective compared to amiodarone [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…We read the full-text and abstracts of the remaining 186 studies, and identified 31 eligible articles . Among these, 24 were in Chinese and the remaining 7 were in English [28][29][30][31][32][33][34] (Fig. 1).…”
Section: Retrieval Strategymentioning
confidence: 99%
See 2 more Smart Citations